Factors Associated with The Risk of Eye Injury on Industrial Welding Workers in the Informal Sector in Barumun District, Padang Lawas Regency - Octavariny, Raisha (Universitas Aisyah Pringsewu, 2020)
Eye injury is an infection or inflammation caused by the entry of objects, substances or other particles into the eye, and can also be caused by continuous exposure to radiation to the eye. One of the jobs that have a potential risk of eye injury is working in welding workshops in the informal sector. This study uses a quantitative method with a cross-sectional approach. Using purposive sampling technique with a population of 44 workers and a sample of 30 workers. Collecting data using questionnaires and interviews. The statistical test in this study used the chi-square which aims to determine the factors associated with the risk of eye injury. The results showed that there was a relationship between the variables of working period and the risk of blindness (0.009) (0.005), there was a relationship between the variable length of exposure and the risk of eye injury (0.001) (0.05), there was no relationship between the variable level of knowledge and the risk eye injury (1,000) (0.05), and there is a relationship between the use of PPE and the risk of eye injury (0.001) (0.05). And it can be concluded that of the 4 (four) variables there are 3 variables that have a potential risk of eye injury to welding workers, and it is hoped that the welding workshop manager will pay more attention to his workers in terms of the use of PPE at work, especially when doing the welding process to minimize the risk. unwanted injury.